2023
DOI: 10.1029/2022ef003387
|View full text |Cite
|
Sign up to set email alerts
|

Projecting the Changes in Multifaceted Characteristics of Heatwave Events Across China

Abstract: A heatwave event can be defined as a spell of consecutive days with extreme high temperature (Fischer & Schär, 2010). Compelling evidence in climate change shows unprecedented warming trend in past decades, leading to extensive intensification of heatwave events around the world (e.g., Coumou & Rahmstorf, 2012;Perkins et al., 2012). The proliferation of heatwave events causes detrimental ecological and environmental impacts, increasing the risk of bush fire and irreversible damage to the ecosystem (e.g., Hughe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(66 reference statements)
1
6
1
Order By: Relevance
“…Despite the overall expansion of heatwaves, the mountains regions remain unaffected by heatwave in all scenarios. This inconsistent with previous studies projecting heatwaves in China that found heatwaves in the mountains of Xinjiang in the future 36 . The discrepancy arises from the chosen method for identifying heatwaves.…”
Section: Conclusion and Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite the overall expansion of heatwaves, the mountains regions remain unaffected by heatwave in all scenarios. This inconsistent with previous studies projecting heatwaves in China that found heatwaves in the mountains of Xinjiang in the future 36 . The discrepancy arises from the chosen method for identifying heatwaves.…”
Section: Conclusion and Discussioncontrasting
confidence: 99%
“…This led to a reduction in crop yields and quality, and an increase in the number of patients suffering from airway diseases and cerebrovascular diseases 35 . According to studies investigating future changes of heatwaves in China, Xinjiang is projected to suffer more frequent and intense heatwaves in the twenty-first century 36 . Although the population density in Xinjiang is lower than that of most parts of China, its rapid population growth and concentrated distribution pattern are projected to more people will be affected by frequent heatwaves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using traditional fixed baseline have indicated that hot extremes are becoming more frequent and severe across China with global warming (e.g. Li et al 2018, Sun et al 2018, Wang and Yan 2021, Ma and Yuan 2023, Wei et al 2023. These results illustrate how the future will change if no measures are taken.…”
Section: Introductionmentioning
confidence: 62%
“…Extreme heat can potentially enhance the risk of other types of disasters, including human mortality, wildfire in forest areas, drought, and reducing agriculture and vegetation productivity (Dadbakhsh et al., 2017; Deng et al., 2018; Kalankesh et al., 2015; Sharafkhani et al., 2020). Although heatwave has been extensively investigated during the recent years (i.e., Jyoteeshkumar Reddy et al., 2021; Keellings & Moradkhani, 2020; Liu et al., 2020; Mazdiyasni et al., 2019; Meque et al., 2022; Modarres et al., 2018; Morabito et al., 2017; Perkins‐Kirkpatrick et al., 2017; Rousi et al., 2022; Wei et al., 2023; Z. Xu et al., 2018), there is no universally accepted heatwave definition which varies among sectors and depends on the purpose of the applications (Gosling et al., 2009). Commonly, heatwaves are defined as consecutive days with temperature exceeding fixed temperature or daily percentile as threshold (Alexander et al., 2006; Anderson & Bell, 2009; Hajat et al., 2006).…”
Section: Introductionmentioning
confidence: 99%